Ineffectiveness of the preventive, protective and resocializing function of the penalty of fine for economic incapacity of the convicted person in the Peruvian criminal system in 2015. - De Amat Peralta, Jorge Alberto (2020)
It is analyzed the various criminal processes where the fine and its effectiveness have been imposed or not in its execution in the field of Peru, as well as a bibliographic doctrinal analysis of the foreign legislations (Foreign doctrine on the function of the penalty of fine) in the countries of Spain, Argentina and Italy. It was intended to know the factor that would determine the high degree of ineffectiveness, as well as identify in which foreign legal systems would be fundamental and effective the penalty of fine in its enforcement mechanism. The present investigation is in the field of legal-propositive, of application type, legal partner. The technique of the survey, the Technique of Observation or Documentary Investigation and comparative analysis of foreign doctrine was applied. The study population were judges, prosecutors in criminal matters in a number of 100 and lawyers also in number of 100, in the city of Tacna. It has been specified that the economic factor is what determines the high degree of ineffectiveness of the execution of the fine in the Peruvian criminal justice system and has been declared prescribed for its non-compliance over time. After having verified the results of the specialized doctrine of the legal systems of Spain, Argentina and Italy, I can affirm that the ineffectiveness of the preventive, protective and re-socializing function of the fine in Peru is due to the economic capacity (factor economic) of the active subject.